ARE ACCOUNTING PRINCIPLES TAUGHT EFFECTIVELY? - Penz, A. J. (The Accounting Review, 1950)
The high school student comes to college with the highest expectations only to be confronted in many cases by a self-conscious, ill-at-ease, and nervous instructor who tries to impress the class with all he knows about accounting rather than to make the subject matter comprehensible to the student. It is quite possible that potential accountants are frightened out of the field by the instructor in principles who points out how "tough" accounting is and how few can pass the first course. If the mastery of accounting principles is difficult, it is the shortcoming of the instructor who fails to simplify his presentation, the merit of the text used notwithstanding. The three major factors contributing to the plight of accounting principles are (1) the low esteem in which the introductory courses are held by the staff, (2) the fallacious assumption that anybody can teach principles of accounting, and (3) the faulty departmental organization. In general, there is no prestige attached to the principles course because the higher ranking and higher paid members of the staff teach only advanced courses. What is the way out of the dilemma which is unfair to the beginner in accounting and unjust to the profession? First of all, the problem has to be recognized and enough courage summoned to take corrective action. The problem is to build up esteem for the introductory courses, and to train and supervise closely the new instructors as well as to delegate authority over these courses to senior staff members.